8. Industrial Design: The Roles and Factors of Aesthetics, Modeling, Styling, Product Brand and Branding in Design/Design Education - Efer Obasuyi Osa-Francis (Sciendo, 2017)
This paper examined the roles and factors of Aesthetics viz-a-viz those of modeling, styling and the product Brand (Branding) as viewed against their fundamental relevance as core ingredients for the actualization of any Design initiative and creative endeavour. These roles, influences and place of Aesthetics (and its allied components, makes up the very soul, content and essence of what the product is all about. Its Form, Shape, Morphological / physical attributes and characteristics. The paper established that the aesthetic components of beauty, colour, shape, (form) fonts, (lettering or typography) and all other general Aesthetic Ambience gives the given product the desired quality/beauty that it exudes to help determine its marketability / profitability as a Brand. The paper also reviewed the aspects /implications of these roles and influences on Design Education alongside highlighting the potentials of the Design Educator - learner experience, while exploiting the Teachers ability to effectively harmonise the various approaches and practices of a functional Design-led Educational programme viz-a-viz piloting such talents/skills achieved to practicable and useful ends as professionals in Design and Technology. The paper also seeks to establish that the roles and factors of modeling styling and Branding of the product which is best exemplified through the adaptation of Design inputs and features such as ornamentation, edge delineation, texture movement/flow of linear form, symmetry or Assymetry of shapes, colour, granularity (of matter/particles large or small) or coarseness, play of light (sunlight) and shade, transcendence (state of being or existence of a product beyond the limits of material experience) and that of total harmony. The paper recommends that for any product Brand to succeed it must incorporate all of the above components together with the inclusion of the other qualities that makes up the intangible content of the Brand such as, Brand Name, Logo, Tagline (catchphrase) the Graphics (elements of Design) Brand Shape, Brand colour, culminating in the establishment of what the Brand mission statement is about, its function, role or job it is intended to perform.